Kant & Moral Character - Hildebrand, C (2017)
This thesis argues that Kant has a viable, intellectualist account of moral character that is much richer and more interesting than has often been thought. This account is consistent with his broader practical philosophy, in particular, his account of moral worth. Chapter one establishes that Kant has a theory of education on which a child’s inclinations are to be trained in preparation for her to grasp the moral law and acquire full moral agency. It argues that his account of habit is complex, recognizing a kind of moral value that is broader than his definition of moral worth. Chapter two argues that sympathy is, for Kant, a primarily cognitive disposition of special importance; this is because it provides knowledge of how the moral law applies in particular circumstances, therefore enabling an agent to fulfill her duties toward others. This chapter also resolves a puzzle concerning Kant’s dual concept of character (as both intelligible and empirical) by drawing an analogy with one account of weakness of will. Chapter three develops an account of moral worth that incorporates these more palatable elements of Kant’s account of moral character with the seemingly more austere elements familiar from the Groundwork. This theory allows for positive, participating inclinations alongside ascriptions of moral worth. Further, it introduces a distinction between full and mitigated moral worth, to account for agents who, for example, act rightly but for confused reasons as in the case of Twain’s Huckleberry Finn. Chapter four responds to two objections to Kant on the basis of moral demandingness, one concerning psychological integration and personal relationships, the other concerning the value of non-moral goods more broadly. It then responds to some objections to his account of the highest good, or the idea of a world in which happiness is distributed in proportion to virtue.